Epithelial cells sense local stiffness via Piezo1 mediated cytoskeletal reorganization - Jetta, Deekshitha; Shireen, Tasnim; Hua, Susan Z. (Frontiers in Cell and Developmental Biology, 2023)
Local substrate stiffness is one of the major mechanical inputs for tissue organization during its development and remodeling. It is widely recognized that adherent cells use transmembrane proteins (integrins) at focal adhesions to translate ECM mechanical cues into intracellular bioprocess. Here we show that epithelial cells respond to substrate stiffening primarily via actin cytoskeleton organization, that requires activation of mechanosensitive Piezo1 channels. Piezo1 Knockdown cells eliminated the actin stress fibers that formed on stiff substrates, while it had minimal effect on cell morphology and spreading area. Inhibition of Piezo1 channels with GsMTx4 also significantly reduced stiffness-induced F-actin reorganization, suggesting Piezo1 mediated cation current plays a role. Activation of Piezo1 channels with specific agonist (Yoda1) resulted in thickening of F-actin fibers and enlargement of FAs on stiffer substrates, whereas it did not affect the formation of nascent FAs that facilitate spreading on the soft substrates. These results demonstrate that Piezo1 functions as a force sensor that couples with actin cytoskeleton to distinguish the substrate stiffness and facilitate epithelial adaptive remodeling.